Cannabinoid CB1 receptor inhibition blunts adolescent-typical increased binge alcohol and sucrose consumption in male C57BL/6J mice - Agoglia, Abigail E. (Pharmacol Biochem Behav, 2016)
Increased binge alcohol consumption has been reported among adolescents as compared to adults in both humans and rodent models, and has been associated with serious long-term health consequences. However, the neurochemical mechanism for age differences in binge drinking between adolescents and adults has not been established. The present study was designed to evaluate the mechanistic role of the cannabinoid CB1 receptor in adolescent and adult binge drinking. Binge consumption was established in adolescent and adult male C57BL/6J mice by providing access to 20% alcohol or 1% sucrose for 4 h every other day. Pretreatment with the CB1 antagonist/inverse agonist AM-251 (0, 1, 3, and 10 mg/kg) in a Latin square design dose-dependently reduced adolescent alcohol consumption to adult levels without altering adult intake. AM-251 (3 mg/kg) also reduced adolescent but not adult sucrose consumption. Adolescent reductions in alcohol and sucrose were not associated with alterations in open-field locomotor activity or thigmotaxis. These findings point to age differences in CB1 receptor activity as a functional mediator of adolescent-typical increased binge drinking as compared to adults. Developmental alterations in endocannabinoid signaling in the adolescent brain may therefore be responsible for the drinking phenotype seen in this age group.